Analysis of Science Textbooks from The Aspect of Scientific Argumentation: Comparing Several Books on The Topic of Heat - Aryanti, Dwi; Siswanto, Siswanto; Juliyanto, Eko; Trisnowati, Eli; Amirul, Muhamad Ardi (Journal of Natural Science and Integration, 2024)
This research aims to analyze the 2013 Curriculum Middle School Science textbooks published by the Ministry of Education and Culture and Erlangga publications used in Indonesia when compared with the Lower Secondary Science Matters textbooks used in science learning in Singapore in terms of the aspect of scientific argumentation on the topic of heat. This research is qualitative research analyzed using the constant comparison method. The data analysis process was carried out through five stages, namely reduction, organizing, categorization, synthesis and developing working hypotheses. After the organizing stage, a data validity test is carried out using credibility, transferability, anteriority and confirmability techniques. The results of the research found that there were differences in the scientific argumentation aspects of the three textbooks, namely the majority of the Lower Secondary Science Matters textbooks were at level 3, while the majority in the 2013 Curriculum Middle School Science textbooks published by the Ministry of Education and Culture and those published by Erlangga were at level 2. In the Curriculum Science textbooks The 2013 edition of the Ministry of Education and Culture from Indonesia provides more statements accompanied by supporting sentences to prove the truth in the form of data, experiments, observations in daily life, and pictures that illustrate a situation, whereas the Lower Secondary Science Matters textbook provides more statements ( claim) which is accompanied by supporting sentences to prove its truth in the form of data, experiments, observations in daily life, and pictures that illustrate a situation (data), then reinforced by sentences that connect them (warrant).                                                                                        Keywords: scientific argumentation, Toulmin's Argument Pattern (TAP), science textbook.